Learning Online: The Effect of Learning Digital Badges on Learning Outcome - Nasrah; Muchtar, Fitri Yanty; Nitaninnawa, Fathiyah; Ilham, Muhammad (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
During the COVID-19 pandemic, student learning outcomes have decreased. An effort is needed to increase student learning motivation so that student learning outcomes increase. Based on research, giving reward is one way to increase students' learning motivation. Giving digital badges is an economical and fun way to give rewards to students. This research is collaborative research between lecturers and teachers which aims to develop the ability of lecturers and teachers in conducting collaborative research and to support the technology-based Merdeka Learning program. This research is expected to find out the effect of digital badges in online thematic learning on learning outcomes, and can be a solution to the problem of decreasing student learning outcomes which is the main goal of this research. Data collection using the Experimental method with a Quasi-experimental model. The results showed that there was a significant effect of digital badges on students' online thematic learning outcomes. Based on the results of this study, digital badges can be used as a solution to improve student learning outcomes, especially elementary schools.